2023
DOI: 10.1039/d3cp01818k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the anti-counterfeiting applications of long persistent phosphors

Abstract: Counterfeit products have infiltrated numerous regions worldwide, causing substantial damage to the financial interests of individuals, businesses, and countries. Moreover, counterfeit goods can pose a severe risk to human health....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…1–3 In the past few decades, PersL materials as excellent energy storage materials have been developed rapidly due to their widespread use in various applications including anti-fake, information storage and encryption, emergency route signs, biomedical imaging, and low light illumination. 4–11 Especially, Zn 3 Ga 2 Ge 2 O 10 :Cr (ZGGO:Cr) NIR persistent phosphors with strong emission in the range of 650–1000 nm and an unprecedented PersL duration of more than 15 days were reported by Pan et al 12 Since then, many studies on doped ZGGO PersL phosphors were conducted. For example, Wu et al reported on the near-infrared PersL materials ZGGO:0.5%Cr fabricated under different sintering atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 In the past few decades, PersL materials as excellent energy storage materials have been developed rapidly due to their widespread use in various applications including anti-fake, information storage and encryption, emergency route signs, biomedical imaging, and low light illumination. 4–11 Especially, Zn 3 Ga 2 Ge 2 O 10 :Cr (ZGGO:Cr) NIR persistent phosphors with strong emission in the range of 650–1000 nm and an unprecedented PersL duration of more than 15 days were reported by Pan et al 12 Since then, many studies on doped ZGGO PersL phosphors were conducted. For example, Wu et al reported on the near-infrared PersL materials ZGGO:0.5%Cr fabricated under different sintering atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Anticounterfeiting is one effective method to protect the rights and interests of enterprises and consumers, which has been widely applied in recent decades. The anticounterfeiting technologies mainly include radio frequency identification, laser hologram, magnetic response, fluorescent anticounterfeiting, etc. , Fluorescent anticounterfeiting is widely used because of its advantages such as low manufacturing cost, simple design, easy identification, and mass production . However, fluorescent anticounterfeiting materials usually emit single-mode emissions with low anticounterfeiting security.…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, more complex anti-counterfeiting techniques have been developed by increasing the luminescence modes. 8,9 For instance, triple-mode anti-counterfeiting (PL, PersL, and PSL) was realized using Cr 3+ -doped ZAG phosphors 10 and quadruple-mode anti-counterfeiting (PL, PersL, TL, and PSL) was realized using Mn 2+ ,Cr 3+ -co-doped ZGO phosphors. 11 It is important to note that luminescence presents many forms, including steady, transient and dynamic luminescence.…”
Section: Introductionmentioning
confidence: 99%